Peningkatan Karakter Nasionalis Cinta Tanah Air Peduli Sampah Melalui Gerakan Ambil Sampah 15 Menit (GAS 15 M) - Hanik Latifah (JEID: Journal of Educational Integration and Development, 2021)
A great nation is a nation that has a strong character, high competence, and grows and develops well. The students of SDN Kasin Kota Malang are less concerned about the environment. One way to solve this problem is with 15 Minutes of Gerakan Ambil Sampah 15 Menit (GAS15 M) in a week. This type of research is school action research. This research was conducted in 2 cycles. In cycles I and II carried out in several stages, namely planning, action and observation, and reflection. Based on the results of the study showed that from the results of cycle I to cycle II there was an increase in the mean of class 1 (11%), 2 (10%), 3 (12%), 4 (12%), 5 (7%) and class 6 (7). %). While the overall mean based on KKM is 80%. It did prove that through Gerakan Ambil Sampah 15 Menit (GAS 15 M) can increase the nationalist character of love for the country who cares about waste at SDN Kasin Kota Malang. This increase was evidenced by the overall average result in cycle I of 78%, cycle II to 88%, so that there was an increase of 10%.